Diversity and Inclusion in Emergency Management and First Response: Accounting for Race and Gender in Codes of Ethics in the United States. (2nd January 2022) - Stabile, Bonnie; Simon, Katherine; Thornton, Tonya E.; Grant, Aubrey
Abstract : Disparities in outcomes are evident in emergency management interactions, in acute circumstances, like hurricanes or natural disasters, or routine interactions involving first responders, such as traffic stops or patient transport. Women and people of color are disproportionately represented in experiencing adverse effects. In light of observed inequities, this analysis investigates whether codes of ethics articulate the value of equity as a guiding principle. After presenting background evidence on the manifestation of inequities, we reviewed literature on the general nature of codes of ethics and their context in Public Administration and Emergency Management, giving consideration to social vulnerability and cultural competence. The purpose of this inquiry was to examine codes of ethics in various professions comprising the broad field of emergency management and first response within the United States—including that of the American Society for Public Administration—to determine whether they take race and gender into account. As disparities in outcomes are broadly observed, we hypothesized that the terms would be underrepresented. We found that only a small minority of codes make explicit mention of race or gender, and the majority do not mention equity. We also discovered a stronger emphasis on professionalism than on outcomes within the populations served.